Microbial landscape of patients with limited sterile pancreatic necrosis (non-operated) in the different periods of treatment - V. P. Saganov; L. D. Radnaeva; V. Y. Khitrikheev; E. N. Tsybikov; V. P. Budasheev; N. B. Gorbachev; K. V. Nikolaeva; S. B. Butukhanov; D. I. Reshetnikov (Acta Biomedica Scientifica)
Method of gas chromatography - mass spectrometry was used for the study of patients with microbial landscape pancreatonecrosis. In patients with necrotizing pancreatitis concentration of organisms was determined in serum at the admission to the hospital, in the middle of the treatment and at discharge. Increased concentrations of Helicobacter pylori, Herpes, anaerobic bacteria were detected in the blood serum of patients with limited sterile pancreatic necrosis who had medical diagnostic laparoscopy. This fact, in our opinion, extends the etiology of this disease. We found that patients with pancreatic necrosis has limited sterile dysbiosis, which can be adjusted over time by gas chromatography - mass spectrometry.